Peningkatan Prestasi Belajar Matematika Siswa Sekolah Dasar dengan Media Tangga Pintar - Desi Setiyadi; Henine Cahyasari (Dawuh Guru: Jurnal Pendidikan MI/SD, 2023)
Mathematics in everyday life has a significant contribution. Some students still think that mathematics is difficult. The results of observations of mathematics learning achievement in class III are low by 73% of students who have not finished yet. One of the materials considered difficult by students is the unit length and weight material. The purpose of this study is to improve student achievement in the subject matter of units of length and units of weight in mathematics in grade 3 SD NU Insan Cendekia using smart ladder media. This type of research is classroom action research with a cyclical flow of planning, action, observation and reflection. The research subjects were 12 male students and 9 female students in grade 3 of SD NU Insan Cendekia. Instruments in the form of tests, observations, documentation and field notes. Data were analyzed using descriptive analysis. The study used 2 cycles with the result that in the first cycle the average value was 78 with a percentage of 81% of students completing. The average score in cycle II reached 89. 100% of students achieved the KKM score. Based on these results, smart ladder media can improve mathematics learning achievement.